CHANGING FRAMES: ENGAGING MULTIPLE IDENTITIES IN CULTURAL CONFLICTS - Blackmore, Emily (European Scientific Journal, ESJ, 2015)
Border cultures, like Gloria AnzaldÃºaâ€™s Chicano community, provide a unique opportunity to examine the amalgam of two distinct cultures. While attempting to validate both Mexican and U.S. national identities, it is essential to examine the importance of individual and group identities. The article uses a sociological approach to examine the conflict between cultures. How can the people of these two nations create a shared identity? How can cultural intelligence1 improve international relations?